2018
DOI: 10.3390/land7040116
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Optical and Synthetic Aperture Radar Data for REDD+ Applications in Malawi

Abstract: Recent developments in satellite data availability allow tropical forest monitoring to expand in two ways: (1) dense time series foster the development of new methods for mapping and monitoring dry tropical forests and (2) the combination of optical data and synthetic aperture radar (SAR) data reduces the problems resulting from frequent cloud cover and yields additional information. This paper covers both issues by analyzing the possibilities of using optical (Sentinel-2) and SAR (Sentinel-1) time series data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Combining optical and radar time series also significantly improved our land cover classification, with radar data complementing optical data in clouded areas well. Our results support the conclusions of Hirschmugl et al () who reported improved accuracy in the detection of deforestation events in Malawi using time series of Sentinel‐2 and/or Sentinel‐1 data compared to monotemporal data. Steinhausen, Wagner, Narasimhan, and Waske () also found an improved accuracy of land cover mapping in monsoon regions in India when increasing the number of Sentinel‐1 scenes to one Sentinel‐2 scene, but Mercier et al () found little improvement when adding Sentinel‐1 time series to the one Sentinel‐2 scene considered for mapping land cover in a forest–agriculture mosaic in Brazil.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Combining optical and radar time series also significantly improved our land cover classification, with radar data complementing optical data in clouded areas well. Our results support the conclusions of Hirschmugl et al () who reported improved accuracy in the detection of deforestation events in Malawi using time series of Sentinel‐2 and/or Sentinel‐1 data compared to monotemporal data. Steinhausen, Wagner, Narasimhan, and Waske () also found an improved accuracy of land cover mapping in monsoon regions in India when increasing the number of Sentinel‐1 scenes to one Sentinel‐2 scene, but Mercier et al () found little improvement when adding Sentinel‐1 time series to the one Sentinel‐2 scene considered for mapping land cover in a forest–agriculture mosaic in Brazil.…”
Section: Discussionsupporting
confidence: 92%
“…Temporal compositing (Griffiths, van der Linden, Kuemmerle, & Hostert, ; Vancutsem, Pekel, Bogaert, & Defourny, ) of a time series has sometimes been considered to inform land cover mapping, but a large amount of temporal information is lost during this process. Hence, the utility of combining optical and radar satellite image time series for land cover mapping has hardly ever been assessed; known applications include the mapping of agricultural landscapes and the detection of deforestation events (Hirschmugl, Sobe, Deutscher, & Schardt, ; Inglada et al, ; Kuenzer et al, ; Reiche, Verbesselt, Hoekman, & Herold, ). To our knowledge, this type of approach has never been considered for mapping land cover in tropical regions of conservation interest with persistent cloud cover and limited level of seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…We built RF disturbance probability models for each observation of Landsat 8 and Sentinel-1. Because RF classifiers can be used to predict the probabilities of binary responses [70], several studies have used them for probability mapping with remote sensing data (e.g., References [50,71]). In this study, we predicted the probability of forest disturbances, defined as any discrete event that caused a reduction of forest canopy.…”
Section: Rf Disturbance Probability Models For Landsat 8 and Sentinel-1mentioning
confidence: 99%
“…Several studies have investigated the combination of dense time series optical and SAR data using different approaches (e.g., [22,35,48,49]). One approach is to fuse the time series signals from optical and SAR data in the same model [50]. Reiche et al [51] fused Landsat Normalized Difference Vegetation Index (NDVI) and ALOS/PALSAR backscatter to detect deforestation using the correlation between NDVI-PALSAR time series.…”
Section: Introductionmentioning
confidence: 99%
“…By using multi-source data, the classification accuracy is improved compared to single data source. This has been shown, for example, with a combination of optical data and synthetic aperture radar (SAR, Congo Basin and Malawi city, Mzimba) [8,9]. The fusion of different frequencies (L-and P-band) of SAR products has also received much attention in recent years [10][11][12].…”
Section: Introductionmentioning
confidence: 99%